Impact of Cardiac Implantable Electronic Device Infection: A Clinical and Economic Analysis of the WRAP-IT Trial. (May 2020) - Wilkoff, Bruce L.; Boriani, Giuseppe; Mittal, Suneet; Poole, Jeanne E.; Kennergren, Charles; Corey, G. Ralph; Love, John C.; Augostini, Ralph; Faerestrand, Svein; Wiggins, Sherman S.; Healey, Jeff S.; Holbrook, Reece; et al.
Abstract : Background: Current understanding of the impact of cardiac implantable electronic device (CIED) infection is based on retrospective analyses from medical records or administrative claims data. The WRAP-IT (Worldwide Randomized Antibiotic Envelope Infection Prevention Trial) offers an opportunity to evaluate the clinical and economic impacts of CIED infection from the hospital, payer, and patient perspectives in the US healthcare system. Methods: This was a prespecified, as-treated analysis evaluating outcomes related to major CIED infections: mortality, quality of life, disruption of CIED therapy, healthcare utilization, and costs. Payer costs were assigned using medicare fee for service national payments, while medicare advantage, hospital, and patient costs were derived from similar hospital admissions in administrative datasets. Results: Major CIED infection was associated with increased all-cause mortality (12-month risk-adjusted hazard ratio, 3.41 [95% CI, 1.81–6.41]; P <0.001), an effect that sustained beyond 12 months (hazard ratio through all follow-up, 2.30 [95% CI, 1.29–4.07]; P =0.004). Quality of life was reduced ( P =0.004) and did not normalize for 6 months. Disruptions in CIED therapy were experienced in 36% of infections for a median duration of 184 days. Mean costs were $55 547±$45 802 for the hospital, $26 867±$14 893, for medicare fee for service and $57 978±$29 431 for Medicare Advantage (mean hospital margin of −$30 828±$39 757 for medicare fee for service and −$6055±$45 033 for medicare advantage). Mean out-of-pocket costs for patients were $2156±$1999 for medicare fee for service, and $1658±$1250 for medicare advantage. Conclusions: This large, prospective analysis corroborates and extends understanding of the impact of CIED infections as seen in real-world datasets. CIED infections severely impact mortality, quality of life, healthcare utilization, and cost in the US healthcare system. Registration: URL: https://www.clinicaltrials.gov Unique Identifier: NCT02277990 Abstract : Supplemental Digital Content is available in the text.